Perancangan Aplikasi Pengenalan Adat dan Budaya Betawi Berbasis Android - Dona Katarina; Ahmad Husain; Hafiz Yusuf (Program Studi Informatika, Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2020)
The research objective is to introduce Betawi customs and culture with an android application system that makes it easier for people and the younger generation to continue to preserve Betawi culture. The research method uses grounded research, which is a research method based on facts and uses comparative analysis with the aim of making empirical generalizations, establishing concepts, proving theories, developing theories, collecting and analyzing data at the same time. After the author analyzes and collects data, finally the author can draw the conclusion that with this application system, it can help introduce and educate the public more broadly in the introduction of Betawi customs and culture.